Disk and file management tasks on HP-UX - Madell, Tom (Hewlett-Packard Professional Books, 1997)
Specifically designed to help advanced system administrators get the most out of their HP-UX systems. This book introduces the basics of disk management and logical volumes in HP-UX systems. It presents hard-to-find information about HP-UX file system management, and the new Journaled File System. It covers advanced logical volume management (LVM) tasks, including managing root, swap and dump, and shows how to convert and troubleshoot logical volumes. Other topics include LVM data mirroring and disk striping. This book is primarily intended for advanced HP-UX System Administrators and other UNIX system administrators, and will also serve the needs of HP workstation users who must also perform administration tasks.